Trade of agricultural real estate in the light of recent changes implemented by the act of 14 April 2016 – selected issues - Mikołajczyk, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The article analyses some specific problems of the civil turnover of agricultural real estate in the Polish legal system. The basic aim of my research is to give a relatively clear answer to the question asked about the significance of the civil turnover of agricultural real estate. Taking into consideration a hybrid character of the specific solutions, the aim will be to organize somehow the analyzed legal regulation of the turnover of agricultural real estate, to identify a key notion and to formulate regularities governing the legal form of the turnover combined with administrative interference (in the form of an administrative decision) against their wider context. By referring such observations to the problem of the role of an administrative decision in the civil turnover of agricultural real estate, different questions can be raised, concerning: sense of creating a special regulation of the turnover of agricultural real estate in the Polish legal system, the placement of such a regulation and its effectiveness in the formation of the agricultural system – or even the social and economic system – especially in new conditions where the ”driving force” of the development of the Polish agricultural law is also the European law.